Phaeton’s Flight, Adonis’s Trial, and Minerva in the House of Envy: Lodovico Dolce between Ovid and Ariosto - Torre, Andrea (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2016)
Introducing Thyeste: Tragedia da Seneca (1547), the Venetian writer Lodovico Dolce (1508–68) defines the art of translating a book as an experience that lives in the “perspective of the becoming [...] because in order to translate, it is necessary for us to take another language or (if possible) another human nature.” This article presents three case studies where the nexus between Ludovico Ariosto’s Ovidianism and Dolce’s Ariostism becomes an example of the stylistic and editorial relationship between word and image, as well as a paradigmatic explanation of the dynamics and strategies of reception in the early age of print. The aims of this exercise are the following: (1) to investigate the important mediation of Ariosto’s epic-chivalric model for the translation of the classics into vernacular and for the “canonization” of texts through their publication; (2) to study the man-to-man combat between Dolce’s writing, Ariosto’s pattern, and Ovid’s Metamorphoses, and the way it develops from the Stanze nella favola di Venere e Adone (1545) to the thirty cantos of the poem Le Trasformazioni (1553); (3) to analyze the history of the illustrations in Ariosto’s Cinque canti from the perspective of the interaction between words and images, modes of writing and reading, and modes of invention and reception.